Metode Routing Protokol LEACH pada Jaringan Sensor Nirkabel Studi Kasus Sistem Pemantauan Suhu dan Kelembaban Udara - Raden Sumiharto; Rosyidatul Ilma; Rif’Atunnisa Rif’Atunnisa (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2019)
Wireless Sensor Network (WSN) is a wireless network consisting of a group of nodes scattered in a certain area. Each node has the ability to gather data around it and communicate with other nodes. In WSN, energy efficiency is important to maintain the lifetime of a network. A WSN consisting of several clusters and having a Cluster Head (CH) in each cluster requires a CH change mechanism in each cluster so that the network lifetime is longer.The LEACH algorithm is implemented on a system consisting of 9 sensor nodes and 1 sink node. Each sensor node monitors the temperature and humidity of the surrounding air. System testing is done by varying the number of data snippets per CH selection process in each LEACH cycle. Based on the results of testing, the application of the LEACH algorithm can increase network lifetime. The LEACH algorithm with 70 data snippets is an optimal state that results in a network lifetime of 7,387 seconds, whereas with the same number of data snippets when using a non-LEACH algorithm the network lifetime can only reach 5,565 seconds.